Hubungan Antara Perbandingan Sosial dan Citra Tubuh Remaja Laki-Laki Pada Pengguna Media Sosial di Kota Makassar - Sariana Abdullah; Eva Meizara Puspita Dewi (INDONESIAN COUNSELING AND PSYCHOLOGY, 2023)
Adolescence begins to encourage individuals to shape their body image, including the male gender. However, the influence of social media in comparing themselves with other individuals greatly affects the concept of body image they have. The study was to determine the relationship between social comparison and body image of male adolescent social media users in Makassar City. The participants of this study were male adolescents aged 12-22 years and were social media users in Makassar City. This study uses a scale adapted from The Multidimensional Body-Self Relations Questionnaire (MBSRQ) Users' Manual-Third Revision by Cash (2000) and an Upward and Downward Psychological Appearance Comparison scale from O'Brien (2009) which was adapted and developed by Setiawati (2020). This research was tested using the Spearman Rho data analysis technique. The study found that there was a negative relationship between social comparison and body image in male adolescent social media users in the city of Makassar (p = 0.012, r = -0.209). This study illustrates that the higher the social comparison, the lower the body image of male adolescent social media users in the city of Makassar. This research can be a reference and information about the negative and positive relationship of social comparisons in terms of appearance on social media to the body image of adolescent males in Makassar City.